Lagrangian Stability of a Class of Second-Order Periodic Systems - Shunjun Jiang; Fang Fang (Abstract and Applied Analysis)
We study the following second-order periodic system: x′′+V′(x)+p(t)=0 where V(x) has a singularity and p(t)=p(t+1). Under some assumptions on the V(x) and p(t), by Moser's twist theorem we obtain the existence of quasiperiodic solutions and boundedness of all the solutions.